Interspeech 2016 2016
DOI: 10.21437/interspeech.2016-346
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Turn-Taking Cues

Abstract: This paper investigates to what extent breathing can be used as a cue to turn-taking behaviour. The paper improves on existing accounts by considering all possible transitions between speaker states (silent, speaking, backchanneling) and by not relying on global speaker models. Instead, all features (including breathing range and resting expiratory level) are estimated in an incremental fashion using the left-hand context. We identify several inhalatory features relevant to turn-management, and assess the fit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…By contrast, [2] found that inhalation tends to be deeper in turn-holding than in turn-changing pauses, although the size of this effect seemed to be rather small. By including an additional category of backchannel-like utterances in our own work we have been able to identify consistent variation in inhalation amplitude across turn-categories [3]. We also found that relatively increased lung volume at the inhalation onset cued speech inhalations, which we hypothesized to be a strategy for arriving at timely speaker transition.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations
“…By contrast, [2] found that inhalation tends to be deeper in turn-holding than in turn-changing pauses, although the size of this effect seemed to be rather small. By including an additional category of backchannel-like utterances in our own work we have been able to identify consistent variation in inhalation amplitude across turn-categories [3]. We also found that relatively increased lung volume at the inhalation onset cued speech inhalations, which we hypothesized to be a strategy for arriving at timely speaker transition.…”
Section: Introductionsupporting
confidence: 52%
“…When fBL (·) is implemented as a Jelinek-Mercer-smoothed n-gram model as described in [15], the cross-entropies for TRAINSET and TESTSET are 0.256 bits/100ms and 0.239 bits/100ms, respectively; these are shown as baseline "1" in Figure 2. Baseline "2" represents an NN-based MI implementation [6] as described in Subsection 2.3; as for all other NNs in this article, we used J = 32 hidden units (decided using TRAINSET), with one hundred iterations of scaled conjugate gradient (SCG) pre-training 3 and one thousand iterations of SCG training. The performance of baselines "1" and "2" differs only negligibly 4 .…”
Section: Baseline Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that REL is heavily influence by posture shifts, it was estimated following a procedure we proposed in Włodarczak and Heldner (2016b). Specifically, REL was taken as the mean level of troughs in the previous 20 respiratory cycles.…”
Section: Methodsmentioning
confidence: 99%